SOCIAL SUPPORT OF SOCIAL AND PSYCHOLOGICAL SERVICES OF MILITARY YOUTH, WORK FORMS (Psychology Travelogs, 2022)
Psychological work is a concerted, purposeful activity of military psychologists, other officials of personnel agencies, commanders (chiefs), staffs with regard to the formation of psychological qualities in military personnel that ensure the performance of tasks in various conditions, the preservation of the mental health of military personnel, their members families, employees of the Armed Forces of Ukraine.The experience of organizing psychological work convincingly shows that among military personnel there are persons who need increased social psychological attention and individual psychological help (support) to overcome personal psychological problems.The main areas of work in providing social psychological help and support to servicemen are to determine the essence of their psychological problems as precisely as possible through social and psychological study and psychological examination; determination of ways to solve these problems (as a rule, through the creation of an individual program of psychocorrective and/or training measures); implementation of certain methods in the form of specific psychological influence and, as the main goal of such work, achieving stabilization and positive dynamics of psycho-emotional states.
Keywords: social psychological assistance; psychological hygiene; psychological problems; psychological work